A Study On The Cleaning Methods Of Stone Artifacts. - Stephen, Dr. Chia (2002)

(untitled)
Stone has been one of the earliest materials used by man since prehistoric times to make tools, implements and art objects. In recent times, these stone artifacts have formed a large part of the collections in museums, temples, churches, and homes of private collectors. Stone artifacts, though strong and durable, disintegrate in time due to various deteriorating factors such as heat, the presence of micro-organisms, salts, algae, water, acids, dust, stains and mishandling.